PENGARUH PENGGUNAAN ZEP QUIZ TERHADAP HASIL BELAJAR PAI PADA PESERTA DIDIK KELAS VII B DI SMP NEGERI 1 KARAWANG BARAT - Sinta Devi, Irena; Taufik Mustofa; Makbul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examined the effect of ZEP Quiz, a gamified digital quiz platform, on Islamic Religious Education learning outcomes among seventh-grade students. A one-group pretest-posttest design involved 38 students of class VII B at SMP Negeri 1 Karawang Barat. Learning outcomes were measured using a ten-item test, while 37 students completed a 15-item perception questionnaire with acceptable reliability (Cronbach’s alpha = .771). Data were analyzed using descriptive statistics, the Shapiro-Wilk test, a paired-samples t test, and Cohen’s dz. The mean score increased from 46.58 to 87.89, with a significant mean gain of 41.32 points, t(37) = 8.01, p < .001, and a large effect size (dz = 1.30). Student perceptions were positive, with 56.8% in the high category and 43.2% in the moderate category. ZEP Quiz was associated with improved learning outcomes and positive student responses. However, the absence of a control group and the short intervention period limit causal conclusions.